A comparative legal study of the war power in the constitutions of Australia, Canada, and the United States - Murphy, E (1951)
﻿ It is the object of this dissertation to consider, as a problem of constitutional law, the nature and scope of the war power of the central government in Australia, Canada, and the United States. The war power is something of an anomaly in federal constitutional law. In exercising it the central government may transcend the federal division of powers which is described in the organic law, and, to an extent which varies with the degree of emergency which is present, may invade an area which is normally reserved to the regional governments. Under conditions of an emergency attributable to war, the central government may also enact war legislation which in normal times would be considered to fall within the prohibition of a constitutional limitation. The constitutional systems of Australia, Canada, and the United States exhibit, sufficient similarities to make a comparative study of the war power profitable. In each the wax power is entrusted to the central government; in each the regional governments possess other reserved powers which in normal times may not be exercised by the central government; in each the federal judiciary has the last word in interpreting a written constitution. But certain basic dissimilarities dictate the pattern which this comparative study must follow. [Please see pdf. for full abstract.]